Assessing the role of family level variation and heat shock gene expression in the thermal stress response of the mosquito Aedes aegypti. (27th March 2023) - Ware-Gilmore, Fhallon; Novelo, Mario; Sgrò, Carla M.; Hall, Matthew D.; McGraw, Elizabeth A.
Abstract : The geographical range of the mosquito vector for many human disease-causing viruses, Aedes aegypti, is expanding, in part owing to changing climate. The capacity of this species to adapt to thermal stress will affect its future distributions. It is unclear how much heritable genetic variation may affect the upper thermal limits of mosquito populations over the long term. Nor are the genetic pathways that confer thermal tolerance fully understood. In the short term, cells induce a plastic, protective response known as 'heat shock'. Using a physiological 'knockdown' assay, we investigated mosquito thermal tolerance to characterize the genetic architecture of the trait. While families representing the extreme ends of the distribution for knockdown time differed from one another, the trait exhibited low but non-zero broad-sense heritability. We then explored whether families representing thermal performance extremes differed in their heat shock response by measuring gene expression of heat shock protein-encoding genes Hsp 26, Hsp83 and Hsp70. Contrary to prediction, the families with higher thermal tolerance demonstrated less Hsp expression. This pattern may indicate that other mechanisms of heat tolerance, rather than heat shock, may underpin the stress response, and the costly production of HSPs may instead signal poor adaptation. This article is part of the theme issue 'Infectious disease ecology and evolution in a changing world'.